Curriculum Implementation in Surabaya Schools: Approaches, Challenges and Innovations - Dwirisnanda, Danis Ade (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study explores the implementation of curriculum in various schools in Surabaya, including SMP Wachid Hasyim 7, SMA Al-Falah, and SMK PGRI 7, with a focus on the use of Merdeka Curriculum and 2013 Curriculum. The study also examines the integration of technology, the application of inclusive concepts, and collaboration and evaluation in the learning process. In Surabaya, many schools adopt a combination of Merdeka Curriculum and 2013 Curriculum to meet the dynamic needs of education. The curriculum is developed with philosophical foundations such as Pancasila, humanism, and progressivism, which are adapted to the needs of students and the development of the times. Information and communication technology is integrated into learning to increase effectiveness and interactivity, although some schools still experience limitations in facilities. The application of inclusive concepts in some schools shows positive steps, although there are still challenges in preparing special educators for students with special needs. Collaboration between teachers, students, parents, and the community is strengthened to support the implementation of the curriculum. Evaluation is conducted periodically to assess effectiveness and identify areas for improvement. The results of the study show that schools in Surabaya are trying to implement a curriculum that is adaptive and relevant to the needs of students. However, challenges related to resources and facilities still need to be addressed to achieve optimal implementation. Efforts of collaboration and evaluation conducted periodically are positive steps towards improving the quality of education. Improvements in facilities and resources are needed to support the integration of technology and inclusion, as well as to strengthen collaboration with parents and the community to create a supportive and inclusive learning environment.